Feeling pain for the very first time: the normative knowledge argument - Kahane, G (Wiley-Blackwell, 2010)
In this paper I present a new argument against internalist theories of practical reason. My argument is inspired by Frank Jackson's celebrated Knowledge Argument. I ask what will happen when an agent experiences pain for the first time. Such an agent, I argue, will gain new normative knowledge that internalism cannot explain. This argument present a similar difficulty for other subjectivist and constructivist theories of practical reason and value. I end by suggesting that some debates in meta-ethics and in the philosophy of mind might be more closely intertwined than philosophers in either area would like to believe.